Four-wheel-drive vehicle trajectory tracking control at joint planning layer - Li, Aijuan; Han, Wenyao; Liu, Gang; Huang, Xin; Wang, Xibo; Zhang, Qi (Frontiers in Energy Research, 2022)
Because the real road conditions are complex and changeable, the vehicle cannot drive normally according to the predetermined trajectory. Therefore, for the four-wheel drive electric vehicle, a trajectory tracking control method of joint planning layer is proposed. First, in the process of vehicle trajectory tracking, the obstacle avoidance trajectory is planned for the dynamic obstacle environment. Then, an MPC trajectory tracking controller with a velocity planning module is designed to reduce the lateral acceleration of the vehicle avoiding obstacles at high speed during trajectory tracking. Finally, CarSim/Simulink co-simulation verification and hardware-in-the-loop (HIL) simulation verification are carried out to verify the performance of the controller. The simulation results show that the trajectory planning module can successfully plan the trajectory of obstacle avoidance, and the improved MPC controller can effectively reduce the lateral acceleration of the target vehicle during trajectory tracking; HIL analysis shows that the MPC trajectory tracker with speed planning module can control the vehicle with good driving stability. Trajectory tracking control under urban road conditions will be considered in future research.